Scholarly Contributions of Required Senior Research Projects in a Doctor of Pharmacy Curriculum - Assemi, Mitra (Am J Pharm Educ, 2015)
Objective. To determine dissemination outcomes and faculty perceptions of senior research projects conducted from 2008 to 2011 by PharmD students in a curricular pathway focused on direct patient care. Methods. Preceptors’ reported dissemination outcomes of research projects were surveyed and their perceptions of the precepting experience were rated using a web-based survey. Results were compared to those from an earlier pharmaceutical care cohort (2002-2007) and a combined cohort of 2, more research-intensive curricular pathways at the school. Results. The overall response rate was 90.2%. Project dissemination included 61.3% at an institutional forum, 42.3% as a submitted publication, 37.8% as a poster, and 4.5% as an oral presentation. Projects completed from 2008-2011 were significantly more likely than those from 2002-2007 to be submitted for publication (42.3% vs 10.7%, p<0.001) and published (28.8% vs 5.3%, p<0.001). Most preceptors found their research projects valuable to them professionally (88.3%) and to their own or another institution (83.5% and 78.5%, respectively). Ninety-five percent of preceptors would precept again. Conclusion. Dissemination rates for pharmaceutical care projects increased over time. Despite modest dissemination levels, the majority of preceptors agreed that required student research projects provide a valuable learning experience for students.